2015
DOI: 10.7863/ultra.14.11030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound‐Guided Core Needle Biopsy and Endoscopic Ultrasound‐Guided Fine‐Needle Aspiration for Solid Pancreatic Lesions

Abstract: The diagnostic yield of US-guided CNB for solid pancreatic lesions is superior to that of EUS-guided FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…9 A core biopsy specimen has many supposed advantages over an aspirated cytologic specimen including better diagnostic yield and lower number of needle passes required to collect an adequate sample. [11][12][13] The aim of this study is to compare the diagnostic accuracies of EUS-FNA and EUS-CNB for solid pancreatic mass lesions. [11][12][13] The aim of this study is to compare the diagnostic accuracies of EUS-FNA and EUS-CNB for solid pancreatic mass lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A core biopsy specimen has many supposed advantages over an aspirated cytologic specimen including better diagnostic yield and lower number of needle passes required to collect an adequate sample. [11][12][13] The aim of this study is to compare the diagnostic accuracies of EUS-FNA and EUS-CNB for solid pancreatic mass lesions. [11][12][13] The aim of this study is to compare the diagnostic accuracies of EUS-FNA and EUS-CNB for solid pancreatic mass lesions.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, many studies have been conflicting in terms of examining the ability of CNB to improve diagnostic accuracy and reduce the number of required needle passes. [11][12][13] The aim of this study is to compare the diagnostic accuracies of EUS-FNA and EUS-CNB for solid pancreatic mass lesions. We hypothesize that EUS-CNB is superior to EUS-FNA for the sampling of solid pancreatic masses in terms of diagnostic accuracy and the number of passes required to formulate an accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] In a study evaluating pancreatic mass sampling via EUS-FNA with a 25-gauge needle compared with percutaneous ultrasound-guided CNB using an 18-gauge needle, Sur et al described no significant differences with regard to the accuracy, technical failure rate, sensitivity, or specificity between modalities; however, CNB had a significantly higher diagnostic yield (86%) compared with EUS-FNA (66%). 45 More recent advances in needle technology have enabled the endoscopist to obtain true tissue fragments comparable to CNB specimens from the minimally invasive endoscopic approach, such as the cutting reverse bevel EchoTip ProCore needle (Cook Medical, Bloomington, Ind) or the cutting SharkCore needle (Beacon Endoscopic, Newton, Mass). Although one study demonstrated the superiority of EUS-FNA using a 22-gauge needle compared with 22-gauge EUS-EchoTip ProCore biopsies of solid pancreatic lesions, 43 other publications have described superior diagnostic yield, more cellular cell blocks for ancillary testing, and more specific tumor characterization for EUS-EchoTip ProCore biopsies compared with EUS-FNA specimens.…”
Section: Pancreatic Lesionsmentioning
confidence: 99%
“…EUS‐FNA has a proven track record as a relatively safe procedure for sampling solid pancreatic lesions, with sensitivities and diagnostic accuracies in the range of 80% to 95% . In a study evaluating pancreatic mass sampling via EUS‐FNA with a 25‐gauge needle compared with percutaneous ultrasound‐guided CNB using an 18‐gauge needle, Sur et al described no significant differences with regard to the accuracy, technical failure rate, sensitivity, or specificity between modalities; however, CNB had a significantly higher diagnostic yield (86%) compared with EUS‐FNA (66%) . More recent advances in needle technology have enabled the endoscopist to obtain true tissue fragments comparable to CNB specimens from the minimally invasive endoscopic approach, such as the cutting reverse bevel EchoTip ProCore needle (Cook Medical, Bloomington, Ind) or the cutting SharkCore needle (Beacon Endoscopic, Newton, Mass).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative modality for biopsy of pancreatic lesions is imaging‐guided percutaneous core needle biopsy, which can provide a histologic specimen and does not require an endoscopic procedure or sedation. Computed tomography (CT) and ultrasound (US) are most often used for guiding percutaneous pancreas biopsy . Magnetic resonance imaging (MRI) offers many inherent advantages over CT and US in terms of superior soft‐tissue contrast resolution, blood flow‐empty action, a nonionizing nature, and direct multiplanar capabilities.…”
mentioning
confidence: 99%